Methane in Lakes: Variability in Stable Carbon Isotopic Composition and the Potential Importance of Groundwater Input - Schenk, Jonathan; Sawakuchi, Henrique O.; Sieczko, Anna K.; Pajala, Gustav; Rudberg, David; Hagberg, Emelie; Fors, Kjell; Laudon, Hjalmar; Karlsson, Jan; Bastviken, David (Frontiers in Earth Science, 2021)
Methane (CH4) is an important component of the carbon (C) cycling in lakes. CH4 production enables carbon in sediments to be either reintroduced to the food web via CH4 oxidation or emitted as a greenhouse gas making lakes one of the largest natural sources of atmospheric CH4. Large stable carbon isotopic fractionation during CH4 oxidation makes changes in 13C:12C ratio (δ13C) a powerful and widely used tool to determine the extent to which lake CH4 is oxidized, rather than emitted. This relies on correct δ13C values of original CH4 sources, the variability of which has rarely been investigated systematically in lakes. In this study, we measured δ13C in CH4 bubbles in littoral sediments and in CH4 dissolved in the anoxic hypolimnion of six boreal lakes with different characteristics. The results indicate that δ13C of CH4 sources is consistently higher (less 13C depletion) in littoral sediments than in deep waters across boreal and subarctic lakes. Variability in organic matter substrates across depths is a potential explanation. In one of the studied lakes available data from nearby soils showed correspondence between δ13C-CH4 in groundwater and deep lake water, and input from the catchment of CH4 via groundwater exceeded atmospheric CH4 emissions tenfold over a period of one month. It indicates that lateral hydrological transport of CH4 can explain the observed δ13C-CH4 patterns and be important for lake CH4 cycling. Our results have important consequences for modelling and process assessments relative to lake CH4 using δ13C, including for CH4 oxidation, which is a key regulator of lake CH4 emissions.